Popliteal arterial thrombosis in nephrotic syndrome: a case report. Issue 1 (2nd January 2017) - Tachamo, Niranjan; Dhital, Rashmi; Timilsina, Bidhya; Nazir, Salik; Lohani, Saroj; Poudel, Dilli Ram
ABSTRACT: Thrombosis is a frequent cause of morbidity and mortality in patients with nephrotic syndrome (NS). Though venous thromboses are common in NS, arterial thromboses are relatively rare. Commonly involved arteries include coronary, iliac, femoral, renal, cerebral, pulmonary, mesenteric, and axillary arteries, and the aorta. Arterial thromboses are associated with poor prognosis; treatment options are limited and patients may not always be amenable to treatment. We present the case of a 39-year-old female with NS who presented with thigh pain and was found to have sub-acute popliteal artery thrombosis.